UMKM MARKETING STRATEGY IN THE ERA OF DIGITALIZATION - Endri Haryati; Teguh Setiawan Wibowo; Agus Purbo Widodo (Jurnal Intelek Insan Cendikia, 2024)
UMKM are independent productive business units, carried out by individuals or business entities in all economic sectors. In principle, there is a distinction between Micro Enterprises (UM), Small Enterprises (UK), Medium Enterprises (UM), and Large Enterprises (UB). Media that is displayed online on the internet is called digital media or online media. Online media is broadly defined as any type of material, including text, images, video, and sound, that can only be accessed online The definition of marketing is in the social sphere and the second is in the managerial sphere. Based on the social definition, marketing is defined as a social process in which individuals and groups obtain what they need and what they want through the creation, offering and exchange of the value of the products and services they own freely with other people. Marketing digitalization is an effort to buy and sell goods or services owned by business owners. With the digitalization of marketing, it is hoped that the market for the goods or services they provide will become more widely known and have many interested people. Marketing digitalization is an effort to buy and sell goods or services owned by business owners. With the digitalization of marketing, it is hoped that the market for the goods or services they provide will become more widely known and have many interested people. Marketing strategy is an effort to market a product, be it goods or services, using certain plans and tactics so that the number of sales becomes higher. Digital marketing can simply be defined as an effort to achieve marketing goals through the application of technology and digital media. Digitalization is described as the use of digital technology to innovate business models and provide new value creation opportunities in the industrial ecosystem. Rapid business development in Indonesia has increased competition between business actors. Several things need to be considered so that the marketing process in UMKM runs well and efficiently, namely that you must pay attention to factors including Marketing Strategy, Integration of Knowledge Sources on Digital Platforms, Consumer Purchase Interest and Income in Digital Marketing, Use of Digital Platforms in UMKM Business, Development of External Understanding and Collaboration.